The Opportunities of the Performance-based Publication Model in Hungary - Sasvári, Péter; Teleki, Bálint; Urbanovics, Anna (Public Finance Quarterly, 2021)
The performance-based publication model is a direct rewarding system among the scientific community, referring to the reward that authors receive for their publications. The amount of the reward depends on the citation index level of the journal in which a given article is published. Based on international best practices, the paper aims to investigate the possibilities of the implementation of this publication model within the Hungarian context. The model’s main advantage is that rewarding takes place at the individual level so its distribution is independent from the institutional level. After reviewing the best practices used in various countries worldwide, an empirical analysis is carried out which is based on the total number of publications in Hungary in 2019 indexed by Scopus. It means a total of 12,281 publications, based on scientometric indicators. Two models are used, model A considers the Hungarian co-authorship rate of the publications while model B takes the amount of the reward into account based on the publication without the co-authorship rate. Results show that in Hungary, the disciplines of Medicine and Engineering are the most competitive at an international level where we find a high proportion of highly indexed Q1 and Q2 publications. Beside these, results demonstrate the dominance of multiple authorship and journal articles in the research sample. As a conclusion, the proposed publication model could be implemented within the Hungarian context, based on the analysis, its estimated cost would be around 6 billion Hungarian forints.